Asphalt-based hard carbon material, preparation method thereof and sodium ion battery

CN122977349APending Publication Date: 2026-10-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510525010.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0018]通过上述技术方案,本公开提供一种沥青基硬碳材料及其制备方法和钠离子电池,该方法通过将沥青与生物质碳源混合,并向其中加入催化剂,能够促使沥青和生物质碳源的分子链充分展开,并发生交联反应;采用梯度升温的固化条件,有利于形成较多的三维交联结构,抑制碳化过程中形成较大的石墨片层,并最终形成具有较多孔道结构的硬碳材料。该硬碳材料具有较高的储钠容量,将其作为钠离子电池的负极材料时,能够有效提高电池的可逆容量,并且具有较高的循环稳定性。本公开的方法不需对生物质碳源进行单独处理,即能将低价值的沥青和生物质碳源转化成高价值的硬碳材料,具有制备过程简单的特点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977349A_ABST
    Figure CN122977349A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a pitch-based hard carbon material, a preparation method thereof and a sodium ion battery, the method does not need to separately treat a biomass carbon source, but converts a low-value pitch and the biomass carbon source into a high-value hard carbon material through a gradient heating mode, and the hard carbon material can effectively improve the reversible capacity of the battery and has high cycle stability when used as a negative electrode material of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of materials, specifically to a pitch-based hard carbon material, a method for preparing the same, and a sodium-ion battery. Background Technology

[0002] Currently, lithium-ion batteries have the highest commercialization rate among commercial electrochemical energy storage devices. However, due to the limited and uneven distribution of global lithium resources and high mining costs, most lithium resources are concentrated in South America. In contrast, sodium-ion batteries have advantages such as abundant resources, low cost, and high safety, and are therefore considered the most competitive large-scale energy storage device for future development. However, sodium-ion batteries are currently in the early stages of technology research and development and industrialization, and their material system is not yet finalized. Therefore, their large-scale application still depends on the selection and rational design of electrode materials.

[0003] Hard carbon, also known as non-graphitized material, refers to materials that are difficult to graphitize even at temperatures above 2500℃, and are generally obtained through heat treatment within the range of 500℃ to 1500℃. Due to its advantages such as high specific capacity, high chemical stability, environmental friendliness, and abundant resources, hard carbon materials are considered ideal anode materials for sodium-ion batteries. Currently, the development of hard carbon anodes mainly follows three technical routes: bio-based, polymer resin-based, and pitch-based. Bio-based precursors can be selected from coconut shells, starch, walnut shells, etc.

[0004] Asphalt, due to its high carbon content and abundant resources, is considered a promising carbon precursor. However, because asphalt is rich in aromatic hydrocarbon structures, it easily forms graphite-like structures during carbonization, resulting in low product capacity (not exceeding 300 mAh / g) and poor tunability, limiting its application to low-end battery products. Furthermore, the current preparation process for asphalt-based hard carbon anodes is relatively complex. For example, some companies use hydrogen peroxide and nitric acid to crosslink asphalt molecules to develop hard carbon materials, which has become a key technical problem restricting the development of asphalt-based hard carbon materials. Therefore, developing a simple and easy-to-implement asphalt-based hard carbon fabrication process has broad application prospects.

[0005] CN116826003A discloses a method for producing hard carbon materials by mixing asphalt and biomass. This method requires separate treatment of the hard carbon precursor before calcination, and the preparation process is relatively complex. The reversible capacity of the obtained hard carbon material as a negative electrode of Na-ion batteries is 260~280mAh / g.

[0006] In summary, current methods for producing asphaltene hard carbon require separate processing of biomass precursors to obtain a suitable structure before mixing them with asphaltene to produce hard carbon materials. The production process also requires the treatment of impurities contained in the biomass itself, making the preparation process quite complex. Summary of the Invention

[0007] The purpose of this disclosure is to provide an asphalt-based hard carbon material, a method for preparing the same, and a sodium-ion battery. This method does not require separate processing of the biomass carbon source, but rather converts low-value asphalt and biomass carbon source into high-value hard carbon material through a gradient heating process. When used as the negative electrode material of a sodium-ion battery, this hard carbon material can effectively improve the reversible capacity of the battery and has high cycle stability.

[0008] To achieve the above objectives, the first aspect of this disclosure provides a method for preparing pitch-based hard carbon materials, the method comprising: S1. Mix and react the pretreated asphalt, biomass carbon source and catalyst to obtain cross-linked products; S2. The crosslinked product is cured by gradient heating to obtain a cured product. The gradient heating conditions include: under an inert gas atmosphere, the crosslinked product is sequentially heated to a first temperature and held for a first time, heated to a second temperature and held for a second time, and heated to a third temperature and held for a third time, wherein the first temperature, the second temperature, and the third temperature are each independently less than 500°C. S3. The cured product is oxidized and carbonized.

[0009] Optionally, in step S1, the mass content of mechanical impurities in the pretreated asphalt is less than 0.05%, and the metal content is less than 50 μg / g.

[0010] Optionally, the raw materials for the pretreated asphalt include coal-based asphalt and / or petroleum-based asphalt. The coal-based asphalt includes coal tar pitch and direct coal liquefaction pitch, and the petroleum-based asphalt includes one or more of vacuum residue asphalt, deoiled asphalt obtained by solvent deasphalting of vacuum residue, catalytic cracking slurry asphalt, and ethylene tar pitch. The biomass carbon source includes monosaccharides and / or polysaccharides, wherein the monosaccharides include glucose and the polysaccharides include starch; preferably, the starch includes dialdehyde starch and / or gelatinized starch; The catalyst comprises inorganic acids and / or organic acids, wherein the inorganic acids include one or more of phosphoric acid, sulfuric acid, carbonic acid and nitric acid, and the organic acids include one or more of sulfonic acid, carboxylic acid and amino acids.

[0011] Optionally, in step S1, the weight ratio of the pretreated asphalt to the biomass carbon source is 1:(0.2~5), and the weight ratio of the pretreated asphalt to the catalyst is 1:(0.05~0.5). The mixing conditions include: mixing the pretreated asphalt with the biomass carbon source and heating to 80-150°C, then adding a catalyst and maintaining the temperature for 5-60 minutes to obtain the crosslinked product; or, The pretreated asphalt is mixed with a biomass carbon source and heated to 80-140°C. Then, a catalyst is added and the temperature is further increased to 130-200°C and held for 5-120 minutes to obtain the crosslinked product.

[0012] Optionally, in step S2, the first temperature is 130~190℃, and the first holding time is 2~120min; the second temperature is 200~250℃, and the second holding time is 15~120min; the third temperature is 260~350℃, and the third holding time is 10~120min. The heating rates of the first temperature, the second temperature, and the third temperature are each independently 2~10℃ / min, and the pressure during the gradient heating process is 0.1~0.3MPa.

[0013] Optionally, in step S3, the oxidation conditions include: placing the cured product in a stirred tank, rotary furnace, or fluidized bed furnace under an air or oxygen atmosphere, heating it to 200-400°C at a heating rate of 3-10°C / min, and holding it at that temperature for 0.1-12 hours.

[0014] Optionally, in step S3, the carbonization conditions include: placing the oxidized product in a box furnace or rotary furnace under an inert gas atmosphere, heating it to 1000-1800°C at a heating rate of 3-10°C / min, holding it at that temperature for 1-24 hours, and then cooling it to 10-25°C at a cooling rate of 5-15°C / min. The inert gas includes one or more of nitrogen, helium, neon and argon, preferably nitrogen.

[0015] Optionally, the method further includes, before the oxidation in step S3, pulverizing the cured product using an air jet mill or a ball mill, and then oxidizing the pulverized product. The particle size of the pulverized product is 2-5 μm for D10, 5-10 μm for D50, and 15-20 μm for D90.

[0016] The second aspect of this disclosure provides a pitch-based hard carbon material prepared using the method described in the first aspect of this disclosure.

[0017] This disclosure provides a sodium-ion battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode comprises the pitch-based hard carbon material described in the second aspect of this disclosure.

[0018] Through the above technical solution, this disclosure provides an asphalt-based hard carbon material, its preparation method, and a sodium-ion battery. The method involves mixing asphalt with a biomass carbon source and adding a catalyst, which promotes the full unfolding of the molecular chains of the asphalt and biomass carbon source, leading to a cross-linking reaction. The use of gradient-temperature curing conditions facilitates the formation of numerous three-dimensional cross-linked structures, inhibits the formation of large graphite sheets during carbonization, and ultimately forms a hard carbon material with a highly porous structure. This hard carbon material exhibits a high sodium storage capacity. When used as a negative electrode material in a sodium-ion battery, it effectively improves the battery's reversible capacity and demonstrates high cycle stability. The method of this disclosure does not require separate processing of the biomass carbon source, thus converting low-value asphalt and biomass carbon sources into high-value hard carbon materials, and is characterized by its simple preparation process.

[0019] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0020] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings: Figure 1 This is a gradient temperature rise curve diagram of step S2 in Embodiment 1 of this disclosure; Figure 2 This is a gradient temperature rise curve diagram of step S2 in embodiment 2 of this disclosure; Figure 3 This is a schematic diagram of the system flow used in Embodiment 1 of this disclosure.

[0021] Explanation of reference numerals in the attached figures 1. Curing reactor 2. Oxidation reactor 3. Carbonization reactor Detailed Implementation The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.

[0022] The first aspect of this disclosure provides a method for preparing pitch-based hard carbon materials, the method comprising: S1. Mix and react the pretreated asphalt, biomass carbon source and catalyst to obtain cross-linked products; S2. The crosslinked product is cured by gradient heating to obtain a cured product. The gradient heating conditions include: under an inert gas atmosphere, the crosslinked product is sequentially heated to a first temperature and held for a first time, heated to a second temperature and held for a second time, and heated to a third temperature and held for a third time, wherein the first temperature, the second temperature, and the third temperature are each independently less than 500°C. S3. The cured product is oxidized and carbonized.

[0023] The method disclosed herein, by mixing asphalt with a biomass carbon source and adding a catalyst, promotes the full unfolding of the molecular chains of the asphalt and biomass carbon source, leading to a cross-linking reaction. The use of gradient-temperature curing conditions facilitates the formation of numerous three-dimensional cross-linked structures, inhibits the formation of large graphite sheets during carbonization, and ultimately results in a hard carbon material with a highly porous structure. This method does not require separate treatment of the biomass carbon source, thus converting low-value asphalt and biomass carbon sources into high-value hard carbon materials, and is characterized by its simple preparation process.

[0024] In one embodiment of this disclosure, in step S1, the mass content of mechanical impurities in the pretreated asphalt is less than 0.05%, and the metal content is less than 50 μg / g, preferably less than 20 μg / g. In the above embodiment, selecting the preferred pretreated asphalt is beneficial for improving the long-term stability of hard carbon materials, thereby improving the cycle performance of the battery.

[0025] In a specific embodiment of this disclosure, the method for preparing the pretreated asphalt may include: filtering the asphalt raw material with a filter having a filtration accuracy of 1~10μm, so that the content of mechanical impurities in the filtered asphalt is less than 0.05%; then, in the presence of a hydrogenation catalyst, mixing the filtered asphalt with a light hydrocarbon raw material for hydrogenation treatment, and fractionating the obtained hydrogenation product to obtain the pretreated asphalt.

[0026] In one embodiment of this disclosure, the raw materials for the pretreated asphalt include coal-based asphalt and / or petroleum-based asphalt. The coal-based asphalt includes coal tar pitch and direct coal liquefaction pitch, and the petroleum-based asphalt includes one or more of vacuum residue asphalt, deoiled asphalt obtained by solvent deasphalting of vacuum residue, catalytic cracking slurry asphalt, and ethylene tar pitch.

[0027] In one embodiment, the biomass carbon source includes monosaccharides and / or polysaccharides, wherein the monosaccharides include glucose and the polysaccharides include starch; preferably, the starch includes dialdehyde starch and / or gelatinized starch. The biomass carbon source of this disclosure can be used in solid form or in solution form. When used in solution form, it can include one or more of starch solution, dialdehyde starch solution, glucose solution, and gelatinized starch solution. The biomass carbon source used in this disclosure has a low impurity content and does not require separate impurity removal treatment, thus featuring a simple preparation process.

[0028] In one embodiment, the catalyst comprises an inorganic acid and / or an organic acid, wherein the inorganic acid comprises one or more of phosphoric acid, sulfuric acid, carbonic acid, and nitric acid, preferably phosphoric acid; the organic acid comprises aliphatic organic acids and / or aromatic organic acids, such as one or more of sulfonic acid, carboxylic acid, and amino acids, preferably p-toluenesulfonic acid. In the above embodiments, by selecting the preferred catalyst, it is beneficial to promote better unfolding of the molecular chains of asphalt and biomass carbon sources, further facilitating cross-linking reactions.

[0029] In one embodiment of this disclosure, in step S1, the weight ratio of the pretreated asphalt to the biomass carbon source is 1:(0.2~5), preferably 1:(0.5~3); the weight ratio of the pretreated asphalt to the catalyst is 1:(0.05~0.5), preferably 1:(0.08~0.3). In the above embodiment, by adopting the preferred weight ratio, it is beneficial to suppress the formation of large graphite sheets by asphaltene molecules during carbonization, thereby facilitating the generation of more porous structures for sodium storage.

[0030] In one embodiment, the mixing conditions include: mixing the pretreated asphalt with a biomass carbon source and heating it to 80-150°C, then adding a catalyst and maintaining the temperature for 5-60 minutes to obtain the crosslinked product.

[0031] In another embodiment, the mixing conditions include: mixing the pretreated asphalt with a biomass carbon source and heating to 80-140°C, then adding a catalyst and continuing to heat to 130-200°C, holding at that temperature for 5-120 minutes to obtain the crosslinked product. In the above embodiment, the temperatures after the two heating cycles are different, and the temperature after the first heating cycle is lower than the temperature after the second heating cycle. Preferably, the temperature difference between the second heating cycle and the first heating cycle is 20-30°C.

[0032] In one embodiment of this disclosure, in step S2, the first temperature is 130~190℃, and the first holding time is 2~120 min; the second temperature is 200~250℃, and the second holding time is 15~120 min; the third temperature is 260~350℃, and the third holding time is 10~120 min. In one embodiment, the heating rates of the first, second, and third temperatures are each independently 2~10℃ / min, and the pressure during the gradient heating process is 0.1~0.3 MPa. In the above embodiments, by adopting preferred curing conditions, it is beneficial to further strengthen the intermolecular bonding force, form a stable three-dimensional network structure, suppress the formation of large graphite sheets during carbonization, facilitate the production of more porous structures, and benefit sodium storage.

[0033] In one embodiment of this disclosure, in step S3, the oxidation conditions include: placing the cured product in a stirred tank, rotary furnace or fluidized bed furnace under an air or oxygen atmosphere, heating it to 200-400°C at a heating rate of 3-10°C / min, and holding it at that temperature for 0.1-12 hours.

[0034] In one embodiment of this disclosure, in step S3, the carbonization conditions include: placing the oxidized product in a box furnace or rotary furnace under an inert gas atmosphere, heating it to 1000-1800°C at a heating rate of 3-10°C / min, holding it at that temperature for 1-24 hours, and then cooling it to 10-25°C at a cooling rate of 5-15°C / min.

[0035] The inert gas disclosed herein includes one or more of nitrogen, helium, neon and argon, preferably nitrogen.

[0036] In one embodiment of this disclosure, the method further includes, before the oxidation in step S3, pulverizing the solidified product using an air jet mill or a ball mill, and then oxidizing the pulverized product; the pulverized product has a D10 particle size of 2~5μm, a D50 particle size of 5~10μm, and a D90 particle size of 15~20μm.

[0037] The second aspect of this disclosure provides a pitch-based hard carbon material prepared using the method described in the first aspect of this disclosure.

[0038] In one specific embodiment, the method of this disclosure is as follows: Figure 3 The process is carried out in the system shown, which includes a curing reactor 1, an oxidation reactor 2, and a carbonization reactor 3. The product outlet of the curing reactor 1 is connected to the material inlet of the oxidation reactor 2, and the product outlet of the oxidation reactor 2 is connected to the material inlet of the carbonization reactor 3.

[0039] The curing reactor 1, oxidation reactor 2, and carbonization reactor 3 disclosed herein are well known to those skilled in the art and will not be described in detail here.

[0040] This disclosure provides a sodium-ion battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode comprises the pitch-based hard carbon material described in the second aspect of this disclosure.

[0041] The pitch-based hard carbon material disclosed herein has the advantages of low raw material price and simple preparation process. It also has a large number of pore structures and high sodium storage capacity. When used in sodium-ion batteries, it can not only improve the reversible capacity of the battery, but also have high cycle stability and can be charged and discharged stably for a long time.

[0042] The present disclosure is further illustrated by the following examples, but the present disclosure is not limited thereto. Unless otherwise specified, all raw materials used in the following examples are commercially available products.

[0043] Example 1 This embodiment is in Figure 3 The process is performed in the system shown, and the specific method is as follows: S1. Pretreated coal direct liquefaction pitch (pretreated pitch) and gelatinized starch (biomass carbon source) were mixed at a weight ratio of 1:0.8 and added to a reactor. The temperature was raised to 100℃ and phosphoric acid was added as a catalyst. The weight ratio of pretreated pitch to catalyst was 1:0.1. The temperature was further raised to 130℃ and then kept at that temperature for 10 min to obtain the crosslinking product. The property analysis data of the pretreated pitch are shown in Table 1.

[0044] S2. The reactor is heated in a gradient to solidify the crosslinked product. The heating process includes: first, heating to a first temperature of 150°C at a heating rate of 2°C / min and holding at that temperature for 60 min; then heating to a second temperature of 200°C at a heating rate of 2°C / min and holding at that temperature for 120 min; finally, heating to a third temperature of 350°C at a heating rate of 2°C / min and holding at that temperature for 120 min. Nitrogen gas is introduced throughout the process, and the pressure is maintained at 0.1 MPa, resulting in the solidified product. The specific heating curve is shown in the figure below. Figure 1 As shown; S3. The cured product is pulverized using an air jet mill to obtain pulverized products with D10 particle size of 3μm, D50 particle size of 8μm, and D90 particle size of 16μm. The pulverized products are then introduced into a rotary furnace for oxidation. Air is introduced during the oxidation process. The oxidation temperature is 320℃, the time is 10h, and the heating rate is 3℃ / min. The oxidized products are then removed and placed in a carbonization furnace for carbonization. The temperature is increased to 1400℃ at a heating rate of 5℃ / min and held for 3h. Then, the temperature is reduced to room temperature at a cooling rate of 5℃ / min to obtain asphalt-based hard carbon material A.

[0045] Table 1 Properties of pretreated coal direct liquefaction bitumen

[0046] Example 2 Same as Example 1, except that: the pretreated asphalt in step S1 is pretreated coal tar pitch, the biomass carbon source is dialdehyde starch, and p-toluenesulfonic acid is added as a catalyst when the temperature is raised to 90°C. The gradient heating process in step S2 is as follows: First, the temperature is increased to a first temperature of 180℃ at a heating rate of 3℃ / min, and held for 30 minutes. Then, the temperature is increased to a second temperature of 210℃ at a heating rate of 3℃ / min, and held for 60 minutes. Finally, the temperature is increased to a third temperature of 330℃ at a heating rate of 3℃ / min, and held for 120 minutes. The specific heating curve is shown in the figure below. Figure 2 As shown; The carbonization temperature in step S3 is 1500℃, resulting in asphalt-based hard carbon material B.

[0047] Example 3 Same as Example 1, except that in step S1, the mass content of mechanical impurities in the pretreated asphalt is 0.02% and the metal content is 30 μg / g, thus obtaining asphalt-based hard carbon material C.

[0048] Example 4 Similar to Example 1, except that in step S1 the weight ratio of pretreated asphalt to biomass carbon source is 1:1, resulting in asphalt-based hard carbon material D.

[0049] Example 5 Same as Example 1, except that in step S2 the first temperature is 250°C, the second temperature is 350°C, and the third temperature is 450°C, to obtain asphalt-based hard carbon material E.

[0050] Example 6 Same as Example 1, except that: in step S3, the D10 particle size of the pulverized product is 10 μm, the D50 particle size is 30 μm, and the D90 particle size is 55 μm, thus obtaining pitch-based hard carbon material F.

[0051] Comparative Example 1 Same as Example 1, except that the curing conditions in step S2 are: heating to 350°C at 5°C / min and holding for 120 min to obtain comparative hard carbon material 1.

[0052] Comparative Example 2 Same as Example 1, except that: the heating process in step S2 includes: first heating to a first temperature of 520°C at a heating rate of 6°C / min, and holding for 5.8 hours, then heating to a second temperature of 780°C, and holding for 5.8 hours, and finally heating to a third temperature of 980°C, and holding for 5.8 hours, to obtain the comparative hard carbon material 2.

[0053] Comparative Example 3 Similar to Example 1, except that step S2 is omitted, and the crosslinked product obtained in step S1 is directly oxidized and carbonized to obtain the comparative hard carbon material 3.

[0054] Test case The hard carbon materials prepared in the examples and comparative examples were mixed with conductive carbon black and a binder to form a slurry, which was then uniformly coated onto aluminum foil and dried to form an electrode. A coin-type sodium-ion battery was fabricated using a sodium metal sheet as the counter electrode, a glass fiber membrane as the separator, and DMC and EC (volume ratio 1:1) as the electrolyte with 1 mol NaClO4 as the electrolyte. The electrochemical performance of the sodium-ion battery was tested on an electrochemical workstation under the following conditions: constant temperature and constant current charge / discharge at 25°C, with a charge / discharge voltage range of 0–2.8V. The test results are shown in Table 2.

[0055] Table 2

[0056] As shown in Table 2, the asphalt-based hard carbon materials prepared using the method disclosed in Examples 1-6 exhibit high sodium storage capacity. When used in sodium-ion batteries, their reversible capacity reaches over 350 mAh / g, and they also demonstrate high charge-discharge cycle stability, retaining over 93% of their capacity after 100 cycles at a current density of 30 mA / g. In contrast, Comparative Examples 1-3, which did not employ the method disclosed in this invention, produced comparative hard carbon materials with poorer performance. Comparative Example 1 used a one-step heating curing process, which easily led to the formation of large graphite sheets during carbonization, resulting in a lower reversible capacity when used in batteries. Comparative Example 2 did not use a curing temperature below 500°C, which is unfavorable for generating hard carbon materials with numerous pores, resulting in a lower sodium storage capacity and thus a lower reversible capacity when used in batteries. Comparative Example 3 did not employ a curing process, resulting in poor cycle stability of the comparative hard carbon material, which could not operate stably in batteries for extended periods.

[0057] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0058] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0059] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A method for preparing pitch-based hard carbon materials, characterized in that, The method includes: S1. Mix and react the pretreated asphalt, biomass carbon source and catalyst to obtain cross-linked products; S2. The crosslinked product is cured by gradient heating to obtain a cured product. The gradient heating conditions include: under an inert gas atmosphere, the crosslinked product is sequentially heated to a first temperature and held for a first time, heated to a second temperature and held for a second time, and heated to a third temperature and held for a third time, wherein the first temperature, the second temperature, and the third temperature are each independently less than 500°C. S3. The cured product is oxidized and carbonized.

2. The method according to claim 1, characterized in that, In step S1, the mass content of mechanical impurities in the pretreated asphalt is less than 0.05%, and the metal content is less than 50 μg / g.

3. The method according to claim 1, characterized in that, The raw materials for the pretreated asphalt include coal-based asphalt and / or petroleum-based asphalt. The coal-based asphalt includes coal tar pitch and direct coal liquefaction pitch. The petroleum-based asphalt includes one or more of vacuum residue asphalt, deoiled asphalt obtained by solvent deasphalting of vacuum residue, catalytic cracking slurry asphalt, and ethylene tar pitch. The biomass carbon source includes monosaccharides and / or polysaccharides, wherein the monosaccharides include glucose and the polysaccharides include starch; preferably, the starch includes dialdehyde starch and / or gelatinized starch; The catalyst comprises inorganic acids and / or organic acids, wherein the inorganic acids include one or more of phosphoric acid, sulfuric acid, carbonic acid and nitric acid, and the organic acids include one or more of sulfonic acid, carboxylic acid and amino acids.

4. The method according to claim 1, characterized in that, In step S1, the weight ratio of the pretreated asphalt to the biomass carbon source is 1:(0.2~5), and the weight ratio of the pretreated asphalt to the catalyst is 1:(0.05~0.5). The mixing conditions include: mixing the pretreated asphalt with the biomass carbon source and heating to 80-150°C, then adding a catalyst and maintaining the temperature for 5-60 minutes to obtain the crosslinked product; or, The pretreated asphalt is mixed with a biomass carbon source and heated to 80-140°C. Then, a catalyst is added and the temperature is further increased to 130-200°C and held for 5-120 minutes to obtain the crosslinked product.

5. The method according to claim 1, characterized in that, In step S2, the first temperature is 130~190℃, and the first holding time is 2~120min; the second temperature is 200~250℃, and the second holding time is 15~120min; the third temperature is 260~350℃, and the third holding time is 10~120min. The heating rates of the first temperature, the second temperature, and the third temperature are each independently 2~10℃ / min, and the pressure during the gradient heating process is 0.1~0.3MPa.

6. The method according to claim 1, characterized in that, In step S3, the oxidation conditions include: placing the cured product in a stirred tank, rotary furnace or fluidized bed furnace under an air or oxygen atmosphere, heating it to 200-400°C at a heating rate of 3-10°C / min, and holding it at that temperature for 0.1-12 hours.

7. The method according to claim 1, characterized in that, In step S3, the carbonization conditions include: placing the oxidized product in a box furnace or rotary furnace under an inert gas atmosphere, heating it to 1000-1800°C at a heating rate of 3-10°C / min, holding it at that temperature for 1-24 hours, and then cooling it to 10-25°C at a cooling rate of 5-15°C / min. The inert gas includes one or more of nitrogen, helium, neon and argon, preferably nitrogen.

8. The method according to claim 1, characterized in that, The method further includes, before the oxidation in step S3, pulverizing the cured product using an air jet mill or a ball mill, and then oxidizing the pulverized product. The particle size of the pulverized product is 2-5 μm for D10, 5-10 μm for D50, and 15-20 μm for D90.

9. A pitch-based hard carbon material prepared by the method according to any one of claims 1 to 8.

10. A sodium-ion battery, characterized in that, The sodium-ion battery includes a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode includes the pitch-based hard carbon material as described in claim 9.